The fairer death: executing women in Ohio - Streib, Victor L. (Ohio University Press series on law, society, and politics in the Midwest, 2006)
Capital crimes -- The death penalty for women nationally -- Earliest Ohio death penalty statutes -- The modern death penalty era in Ohio -- Patterns of death sentencing and executions -- Hester Foster : executed on February 9, 1844 -- Anna Marie Hahn : executed on December 7, 1938 -- Dovie Blanche Dean : executed on January 15, 1954 -- Betty Butler : executed on June 12, 1954 -- Sandra Lockett : sentenced in 1975, reversed in 1978 -- Alberta Osborne : sentenced in 1975, reversed in 1978 -- Patricia Wernert : sentenced in 1976, reversed in 1978 -- Benita Smith : sentenced in 1977, reversed in 1978 -- Sharon Faye Young : sentenced in 1983, reversed in 1986 -- Rosalie Grant : sentenced in 1983, commuted in 1991 -- Debra Brown : sentenced in 1985, commuted in 1991 -- Elizabeth Green : sentenced in 1988, commuted in 1991 -- Beatrice Lampkin : sentenced in 1989, commuted in 1991 -- Donna Roberts : sentenced in 2003, now on death row -- Nicole Ann Diar : sentenced in 2005, now on death row -- Executed women, 1803-2005 -- Death-sentenced women, 1973-2005